Evidence of WW and WZ Production with lepton plus jets Final States in pp Collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Nogima, H.; et al. (Amer Physical Soc, 2009)
We present first evidence for WW+WZ production in lepton+jets final states at a hadron collider. The data correspond to 1.07 fb(-1) of integrated luminosity collected with the D0 detector at the Fermilab Tevatron in pp collisions at root s=1.96 TeV. The observed cross section for WW+WZ production is 20.2 +/- 4.5 pb, consistent with the standard model and more precise than previous measurements in fully leptonic final states. The probability that background fluctuations alone produce this excess is < 5.4x10(-6), which corresponds to a significance of 4.4 standard deviations.